2013
DOI: 10.1186/cc12816
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of plasma fibrinogen levels based on hemoglobin, base excess and Injury Severity Score upon emergency room admission

Abstract: IntroductionFibrinogen plays a key role in hemostasis and is the first coagulation factor to reach critical levels in massively bleeding trauma patients. Consequently, rapid estimation of plasma fibrinogen (FIB) is essential upon emergency room (ER) admission, but is not part of routine coagulation monitoring in many centers. We investigated the predictive ability of the laboratory parameters hemoglobin (Hb) and base excess (BE) upon admission, as well as the Injury Severity Score (ISS), to estimate FIB in maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 44 publications
2
65
1
5
Order By: Relevance
“…69 Fibrinogen repletion is increasingly used as hemostatic treatment of trauma-induced coagulopathy, especially with concentrates.…”
Section: Traumamentioning
confidence: 99%
“…69 Fibrinogen repletion is increasingly used as hemostatic treatment of trauma-induced coagulopathy, especially with concentrates.…”
Section: Traumamentioning
confidence: 99%
“…In Rourke's study, coagulopathic patients had 33 % reduction in fibrinogen levels and 58 % reduction when defining coagulopathy as PT >1.2 [28•]. Schlimp retrospectively studied 675 trauma patients and found that in the presence of acidemia (Base Deficit <−6 mmol/L), 81 % had fibrinogen levels <2 g/L and 63 % had levels <1.5 g/L [29]. Taken together, these studies show that fibrinogen depletion is acute and results in coagulopathy, especially in the most severely injured.…”
Section: Fibrinogen Depletionmentioning
confidence: 99%
“…Dies bedeutet, dass bei einem Großteil der Traumapatienten aus dem SR-Hb-Wert auf die entsprechenden Gerinnungsparameter geschlossen werden kann. Eine ähnlich gute Korrelation zwischen SRHb-Wert und den obigen Gerinnungsparametern konnte mittlerweile auch an über 40.000 Patienten des TR-DGU [18] sowie zwischen Hb und Fibrinogen [41] nachgewiesen werden.…”
Section: Grundlegende Entwicklung Des Algorithmusunclassified
“…Grundlage des verwendeten Gerinnungsalgorithmus sind der mithilfe POCBlutgasanalyse ermittelte SR-Hb, dessen Korrelation mit Standardgerinnungsparametern, wie er an dem Patientengut eines überregionalen Traumazentrums [12,13] sowie den Patienten des TR-DGU nachgewiesen werden konnte [18], und dessen Korrelation mit dem Fibrinogenwert bei Schockraumaufnahme [41]. Beispielhaft verdeutlicht .…”
Section: Introductionunclassified